Prevalence and predictors of percutaneous injuries among health workers in Ghana: a cross-sectional study - Philip Apraku Tawiah; Philip Apraku Tawiah; Emmanuel Appiah-Brempong; Paul Okyere; Geoffrey Adu-Fosu; Mary Eyram Ashinyo; Mary Eyram Ashinyo; Florence Shine Edziah; Florence Shine Edziah; Emmanuel Daitey Amesimeku; Emmanuel Daitey Amesimeku; Priscilla Appiah Baffoe (Frontiers in Public Health)
BackgroundPercutaneous injuries (PI) persist as a prevalent healthcare issue, affecting over a third of healthcare workers worldwide on an annual basis. Globally, a few studies have documented the relationship between PI and factors like work pressure and shift systems. Additionally, limited evidence exists on how these factors contribute to this issue specifically in Ghana.ObjectiveThe study examined exposure to PI and its predictors among health workers in Ghana.MethodsAn analytic cross-sectional study involving multiple health facilities in the Greater Accra region was conducted between January 30 and May 31, 2023. A survey was carried out among 602 healthcare workers across 10 public and private hospitals. Study participants were selected using simple random sampling. Analysis was performed using Stata 15 software, and factors associated with PI were identified using log-binomial regression analysis, with a significance level set at p < 0.05.ResultsThe prevalence of PI was 26.9% (95% CI: 23.4–30.6%). More work experience [APR = 0.97 (0.94, 0.99)], being on a mix of day, evening and night shifts [APR = 1.69 (1.26, 2.27)], frequent experience of work pressure [APR = 1.32 (1.00, 1.75)], frequent [APR = 0.59 (0.40, 0.88)], and constant [APR = 0.55 (0.40, 0.7)] adherence to standard precautions were factors significantly associated with PI.ConclusionShift schedules and work pressure contributed to the substantial rate of PI among healthcare workers in Ghana. It is imperative for health authorities to establish and enforce safety policies prioritizing pressure reduction and fostering a safety-oriented culture across all shifts.